TMOD-07. IN SITU MICROSCOPY OF DRUG AND IMMUNE CELL INTERACTIONS AGAINST BIOFABRICATED TUMOR MODELS. (11th November 2019) - McGhee, Eric; Uruena, Juan; Levings, Padraic; van Meter, Kylie; Smolchek, Ryan; Hood, Derek; Flores, Catherine; Mitchell, Duane; Gregory Sawyer, W
Abstract: BACKGROUND & SIGNIFICANCE: Cancer is a disease in 3-dimensions and there is a desperate need for infrastructure and models to study immuno-oncology treatment strategies in 3D. A new culture system for long-duration maturation of patient derived microtumors has been developed. This system enables in situ confocal imaging and movies of T-cells and tumor model interactions, including measurements of T-cell migration, infiltration, and killing. HYPOTHESIS: Biofabrication of 3D microtumors using bioprinting in transparent soft granular gel media can facilitate the precise arrangement and stability of extra-cellular matrix components, tumor, and immune cells while maintaining continuous liquid perfusion. METHODS: The design, development, and validation of a modular negative pressure perfusion system controls the transport of liquid growth medium, drugs, antibodies, growth factors, and metabolic waste management in 3D. In situ confocal fluorescent microscopy measures cell positions, velocities, and viability during experiments. Steady perfusion velocities are controlled through negative pressure, and velocities from 1–100 nm/s can be achieved. RESULTS: Cell motility, adhesion, and dynamic rearrangement of fibroblasts and endothelial cells within a 3D co-culture of microtumors evolved dramatically over the first 72 hours. Tracking of activated CD8+ T-cells revealed super-diffusive motion in the presence of 3D tumors with a range of 250 µm. Activated T-cell migration speeds have been measured to be between 1.3–2.0 um/min in the 3D media, and preliminary estimates of T cell migration forces are on the order of 1 nN. Arrival of CD8+ T-cells to the tumors within the first 30 minutes revealed cell killing which continued for over 3-hours and resulted in a 2-fold reduction in tumor cell numbers. CONCLUSIONS: This integrated system of 3D bioprinting, perfusion culture plates, and confocal microscopy enables in situ 3D studies of cancer biology, immunotherapy, and drug treatment regimens and provides unique insights and measurements of immune cell invasion dynamics in 3D microtumors.